ARP2/3 complex associates with peroxisomes to participate in pexophagy in plants - Martinek, Jan; Cifrová, Petra; Vosolsobě, Stanislav; García-González, Judith; Malínská, Kateřina; Mauerová, Zdeňka; Jelínková, Barbora; Krtková, Jana; Sikorová, Lenka; Leaves, Ian; Sparkes, Imogen; Schwarzerová, Kateřina (Nature plants, 2023)
Actin-related protein (ARP2/3) complex is a heteroheptameric protein complex, evolutionary conserved in all eukaryotic organisms. Its conserved role is based on the induction of actin polymerization at the interface between membranes and the cytoplasm. Plant ARP2/3 has been reported to participate in actin reorganization at the plasma membrane during polarized growth of trichomes and at the plasma membrane-endoplasmic reticulum contact sites. Here we demonstrate that individual plant subunits of ARP2/3 fused to fluorescent proteins form motile spot-like structures in the cytoplasm that are associated with peroxisomes in Arabidopsis and tobacco. ARP2/3 is found at the peroxisome periphery and contains the assembled ARP2/3 complex and the WAVE/SCAR complex subunit NAP1. This ARP2/3-positive peroxisomal domain colocalizes with the autophagosome and, under conditions that affect the autophagy, colocalization between ARP2/3 and the autophagosome increases. ARP2/3 subunits co-immunoprecipitate with ATG8f and peroxisome-associated ARP2/3 interact in vivo with the ATG8f marker. Since mutants lacking functional ARP2/3 complex have more peroxisomes than wild type, we suggest that ARP2/3 has a novel role in the process of peroxisome degradation by autophagy, called pexophagy.
Keywords: aktiny; komplex proteinů 2-3 souvisejících s aktinem; Peroxisomes; peroxizomy; Arabidopsis; proteiny huseníčku; Actin-Related Protein 2-3 Complex; makroautofagie; Actins; Arabidopsis Proteins; Macroautophagy